Determinants of behavioral intention to use tax e-lejar service among salaried group of taxpayer in Kuala Lumpur - Mohd Azuan, Ahmad Bani (2016)
This study is an attempt to investigate taxpayer’s perception and intention to use Inland Revenue Board of Malaysia’s online service known as tax e-LEJAR. Tax e-LEJAR is an online system where taxpayers can check their tax transaction records via internet. The data are collected from a sample of 198 individual salaried group of taxpayers from IRBM, Kuala Lumpur Bandar Branch using a structured questionnnaire. Analysis of data was using multiple regression. Technology Acceptance Model (TAM) is used for this study in determining taxpayers’ acceptance of tax e-LEJAR service. This study revealed that overall perception towards this system is positive with perceived usefulness is the most significant determinant of the behavioural intention to use tax e-LEJAR service. Perceived ease of use although not directly influenced behavioural intention to use but it is the most significant variable that influenced taxpayer’s attitude towards usage of tax e-LEJAR. The effect of perceived ease of use is also significant in perceived usefulness of tax e-LEJAR.